The Development Of Javanese Mysticism In The Suti Novel By Sapardi Djoko Damono - Syahrotul Latifah; Arif Setiawan (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The mysticism that developed in Javanese society was caused by several elements that lay behind it. The purpose of this study is to describe the element of Javanese mysticism developing. The method used in this research is descriptive qualitative analysis method. The source of research data is Suti's novel by Sapardi Djoko Damono. The data in this study are excerpts of dialogue and narration in Suti's novel by Sapardi Djoko Damono. Data analysis techniques were carried out in stages according to Miles and Huberman with steps including: (1) data reduction stages; (2) data presentation stage; (3) conclusions and verification of data. The results of the study are as follows: elements of the development of Javanese mysticism in the novel Suti by Sapardi Djoko Damono found that there were four elements, namely (a) an element of rationality, namely the economic difficulties experienced by villagers to meet their daily needs; (b) the element of value is the form of respect for ancestors by still applying something that has been trusted; (c) elements of tradition in the form of beliefs of sacred tombs and taught from generation to generation from generation to generation; (d) the affective element is imitating factors and village priyayi actions when sowan to the tomb and set an example in accordance with village priyayi. Keyword: element, Javanese mysticism, priyayi, Suti Abstrak Mistisisme yang berkembang dalam masyarakat Jawa disebabkan oleh beberapa unsur yang melatarbelakanginya. Tujuan penelitian ini yaitu mendeskripsikan unsur berkembangnya mistisisme masyarakat Jawa. Metode yang digunakan dalam penelitian ini yaitu metode analisis deskriptif kualitatif. Sumber data penelitian yaitu novel Suti karya Sapardi Djoko Damono. Data dalam penelitian ini berupa kutipan dialog dan narasi dalam novel Suti karya Sapardi Djoko Damono. Teknik analisis data dilakukan secara bertahap menurut Miles dan Huberman dengan langkah-langkah meliputi: (1) tahap reduksi data; (2) tahap penyajian data; (3) tahap penarikan kesimpulan dan verifikasi data. Hasil penelitian sebagai berikut: unsur berkembangnya mistisisme masyarakat Jawa dalam novel Suti karya Sapardi Djoko Damono ditemukan terdapat empat unsur yaitu (a) unsur rasionalitas yakni kesulitan ekonomi yang dialami warga desa untuk memenuhi kebutuhan sehari-hari ; (b) unsur nilai yakni bentuk penghormatan terhadap leluhur dengan masih menerapkan sesuatu yang telah dipercayai; (c) unsur tradisi yakni berupa kepercayaan makam keramat dan diajarkan dari generasi ke generasi secara turun-temurun; (d) unsur afektif yakni faktor meniru adab dan tindakan priayi desa ketika sowan ke makam dan melakukan teladan sesuai dengan priayi desa. Kata kunci: unsur, mistisisme Jawa, priayi, Suti